2019
DOI: 10.1162/opmi_a_00025
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Criterial Vagueness in Inconsistencies

Abstract: Sixty undergraduate students made category membership decisions for each of 132 candidate exemplar-category name pairs (e.g., chess – Sports) in each of two separate sessions. They were frequently inconsistent from one session to the next, both for nominal categories such as Sports and Fish, and ad hoc categories such as Things You Rescue from a Burning House. A mixture model analysis revealed that several of these inconsistencies could be attributed to criterial vagueness: participants adopting different crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…Verheyen et al. (2019) suggested that the inter‐individual differences relate to stable differences between groups that apply different categorization criteria. For example, the level of education (Verheyen & Storms, 2018) or individual traits (Verheyen, Dewil, & Égré, 2018) affect the choice of category criteria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Verheyen et al. (2019) suggested that the inter‐individual differences relate to stable differences between groups that apply different categorization criteria. For example, the level of education (Verheyen & Storms, 2018) or individual traits (Verheyen, Dewil, & Égré, 2018) affect the choice of category criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Following the literature on vagueness and categorization, we suggest that these two types of vagueness could be interpreted as criterial and degree vagueness (Verheyen, Droeshout, & Storms, 2019). Criterial vagueness is a disagreement between participants about the criteria or conditions to classify a given object into a given category (Verheyen et al., 2019). Degree vagueness, in turn, means that individuals agree about the classification criterion but disagree to what extent the given object satisfies this criterion (Verheyen et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They constituted approximately equidistant color patches between a blue and a green prototype. As a result, any interindividual differences in the stimuli's conceptual representation could only be a matter of degree (i.e., the extent to which different color patches are considered instances of blue) and not a matter of criteria, where different participants consider different dimensions as relevant or weigh several underlying dimensions differently to establish category membership (Verheyen, Droeshout, & Storms, 2019; Verheyen & Storms, 2018; Verheyen, White, & Égré, 2019). Moving to more abstract, multidimensional stimuli, as suggested earlier, will allow one to study whether degree and/or criteria differences in conceptual representations affect generalization.…”
Section: Discussionmentioning
confidence: 99%